ANALISIS HUKUM TERHADAP PELAKU AKTIVITAS PIDANA PENCABULAN DAN KEKERASAN ANAK DI BAWAH UMUR (PUTUSAN NO.49/PID.SUS/2019/PN LBB) - Farhana, Farhana; Saputra, Muhammad Fadira; Batubara, Sonya Airini (Universitas Muhammadiyah Ponorogo, 2023)
Often criminal acts occur in human life and that includes their problems. usually this is because of something like their lust that wants a crime. Crimes that can be committed include various kinds of acts of harassment, obscenity and sexual violence. Types of crimes whose actions are in the category of sexual violence such as obscenity have a lot of impact on the victims. The victims besides being harmed they will also experience trauma and high shame. The study that will be carried out uses normative juridical, namely the method used in conducting research in the field of law with steps. This method works by analyzing legal sources in writing and available in the literature. The materials used in this research are laws, research journals, and books that are still relevant to the prevailing problems. This research uses a descriptive approach. where research is based on written rules as they are. Legal research on child abuse has basically been stated in article 76 E of Law no. 35 of 2014 regarding changes to Law NO. 3 of 2002 which deals with child protection. It is clearly stated in article 76 E which reads